Bangladesh’s Take on Restoring the Parliamentary Control over the Judiciary: New Course through the 16th Amendment to the Constitution - Udin, Syed Morshed Rahad (Kathmandu School of Law Review, 2018)
Shortly after its emergence as a nation through a historic struggle for national liberation, Bangladesh formed its constitution in 1972. Since its formation in 1972, the Constitution of Bangladesh has been amended many times. The latest addition to that amendment list is the 16th amendment of the constitution that was endorsed from the parliament on 17th September 2014. The 16th amendment of the constitution brought back an old provision of the impeachment process of Supreme Court judges of Bangladesh replacing Article 96 of the constitution of Bangladesh. Since the passing of the 16th amendment in the parliament of Bangladesh, it has been a hot topic to be discussed under constitutional law. This short article embodies a critical analysis of the 16th amendment of the constitution and an opinion regarding the very issue.DOI: https://doi.org/10.46985/jms.v6i2.214